(3fRgI GdeTJGb aj GNJQGb GdBaGbs - (3GdEOQjSj , eMeO Hf eMeO Hf YHO Gddg Hf EOQjS GdMSfj GdWGdHj, CHh YHO Gddg,J (B560 (3g` s ((3Ydi Hf MSf GdYLei s)
(3ChdgG (B:s
(3Ef gPG GdEbdje eHODg ef LgI GdZQH ef GdHMQ GdZQHi s
(3BNQgG (B:s
(3Ef gPG GdLRA GdYGTQ ef GdEbdje GdSGHY s
(3HgG NQGFWs
(3fSNI NGeSIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B24 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B236s
Keywords: (3GdLZQGajG h GdHdOGfs